Molecular analysis of genetic variation and relationships amongst abalone (Haliotis midae) at the I&J abalone hatchery at Danger Point, Gansbaai, R.S.A. - Lambrechts, Daneel (Stellenbosch : Stellenbosch University, 2012)
Thesis (MSc)--Stellenbosch University, 2002.